Employees’ Job Satisfaction, Cooperative Schemes’ Benefits and Management of Agri-Environmental Institutions in South-West Nigeria - Adeogun, Stephen Oluseun; Adebayo, Olaoluwa Ayodeji (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study investigates the relationship between employees' job satisfaction, cooperative schemes' benefits, and management practices in Southwest Nigeria. Through a mixed-methods approach, data was collected from 339 employees in various cooperatives of four selected agri-environmental institutions in the region. Results indicate that employees commonly access benefits such as loans and savings culture enhancement through cooperative schemes. Moreover, positive perceptions were found regarding cooperative schemes' management, with respondents expressing satisfaction with financial care and member involvement in decision-making. However, while overall job satisfaction levels were moderate, certain areas, such as job pride and recognition, received neutral responses. Correlation analysis revealed a significant positive relationship between cooperative schemes' management and job satisfaction (r = 0.307, p<0.01), while the relationship between cooperative schemes' benefits and job satisfaction was weak and statistically insignificant (r = -0.018, p>0.01). Based on these findings, it is recommended that organizations prioritize enhancing management practices, tailor benefits to employee needs, offer clear career development pathways and promote a positive work environment to improve job satisfaction and organizational success within cooperative schemes.